2008
DOI: 10.1097/rli.0b013e3181690148
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Perfusion Using First Pass Methods for Lung Nodule Characterization

Abstract: CT Perfusion using first pass modeling appears feasible for lung nodule characterization. Given the short acquisition duration used, weaknesses of the modeling methods are exposed. Nonetheless, microvascular characterization in terms of BF, BV, or Kps appears useful in distinguishing malignant from benign nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 39 publications
5
37
0
1
Order By: Relevance
“…The perfusion parameters were refl ected by several factors such as the imaging modality, the tracer, the data acquisition temporal resolution, and the mathematical model, although the same initial time-attenuation curves for the pulmonary nodule and the main trunk of the pulmonary artery in each subject were adapted. Therefore, the signifi cantly good or excellent correlations among PF MS , EF PP , and BV PP were not surprising, and consistent with correlations in a previous report ( 23 ), the signifi cant correlation between the perfusion parameters and SUV max was considered to be due to the biologic activities of nodules, resulting blood supply, glucose metabolism, and hypoxia. Therefore, our study results suggest that perfusion CT indexes could in all of the evaluated dynamic fi rst-pass area-detector CT indexes among the malignant nodules, benign nodules with expected low biologic activity, and benign nodules with expected high biologic activity.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The perfusion parameters were refl ected by several factors such as the imaging modality, the tracer, the data acquisition temporal resolution, and the mathematical model, although the same initial time-attenuation curves for the pulmonary nodule and the main trunk of the pulmonary artery in each subject were adapted. Therefore, the signifi cantly good or excellent correlations among PF MS , EF PP , and BV PP were not surprising, and consistent with correlations in a previous report ( 23 ), the signifi cant correlation between the perfusion parameters and SUV max was considered to be due to the biologic activities of nodules, resulting blood supply, glucose metabolism, and hypoxia. Therefore, our study results suggest that perfusion CT indexes could in all of the evaluated dynamic fi rst-pass area-detector CT indexes among the malignant nodules, benign nodules with expected low biologic activity, and benign nodules with expected high biologic activity.…”
Section: Discussionsupporting
confidence: 73%
“…To our knowledge, however, no attempts have been made to adapt this area-detector CT system for evaluation in a fi rst-pass dynamic perfusion study of pulmonary nodules. Although a few models for multidetector CT assessment of the regional perfusion CT parameters of lung cancer and/or lung parenchyma have been proposed (19)(20)(21)(22)(23), to our knowledge only Sitartchouk et al ( 23 ) have discussed the capability of quantitatively assessed dynamic fi rst-pass perfusion multidetector CT indexes for evaluation of pulmonary nodules. In addition, this system can be used to assess the timeattenuation curves for multiple pulmonary nodules at different positions and the main trunk of the pulmonary artery, which is important for simultaneous quantitative analysis of blood fl ow without helical scanning.…”
Section: Protocol Support and Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several authors have suggested a longer duration of cine acquisition to enable reliable tissue permeability calculations [5,19,20,26,37]. Although a shorter duration of cine phase has radiation dose and computational benefits, progressive shortening of this phase can conceivably also affect the reproducibility of perfusion measurements [19,20,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Another paper showed that even as CT techniques improve, model-based analysis still requires dynamic imaging over an extended period of time that is typically not achievable by CT. Furthermore, dynamic CT suffers from limited coverage on the z-axis with currently only 2 cm [24]. As in previous publications [25], we used a two-dimensional trueFISP sequence to assess existing motion of the lung and embedded lesions.…”
mentioning
confidence: 99%